Guds ord besunget af Grundtvig - Hansen, Uffe (Grundtvig-studier, 1975)
The Word of God, Celebrated by Grundtvig By Uffe Hansen This essay is a series o f interpretations o f not so well-known poems by Grundtvig on the theological foundations common to all Lutheran churches. Throughout his ministry (1810-72) Grundtvig was aware that the expression, the Word o f God, was an ambiguous one. In his hymns therefore he endeavoured to discover how it is to be understood and how it works. These brief interpretations fall into five chapters: the Word as Subject, the Word o f Life, the Word o f the Church, the Written Word, and the Living Voice.In a hymn which originally appeared in Krønike-Rim (Chronicle Rhymes) in 1829, the Church’s foundation is the Creative Word, which has sanctified baptism and the Eucharist (Sang-Værk 1.1). A further investigation of this thought is to be found in a number o f didactic poems which appeared in manuscript form in Grundtvig’s own handwriting in, amongst others, Dansk Ravnegalder in 1860, for which some verses are borrowed for the hymn Vanæret vor Drot kom i sin Grav (Our King Dishonoured was Laid to Rest), no. 236 in the Danish Hymn Book. At the resurrection it was the Creative Word of Goc( that lived again. At Whitsun the Word o f God created His Church, in which Jesus is present as one in all, though invisible for the world. Grundtvig’s particular understanding o f the Word as that which characterizes man had a considerable influence on his thoughts about the Word o f God, as in the poem Ordets Kvaede (The Song of the Word) Sang-Værk (Hymn Work) 5-161. Only words that come from the heart and go to the heart can animate us and bring us the true and necessary enlightenment (Grundtvig also strongly opposes the thought that we have words in order to hide our thoughts - Talleyrand - but agrees with Edward Young’s use o f the word in his poem The Love o f Fame). When a person is touched by the Word of God, he may speak the truth about the invisible, but he will lie when he speaks only from his own inner emotional upheaval, which is not created by God. These lies will be annihilated by the Word o f God at the end o f the world. There is a kinship between the Word of God and the Word o f Man; it is the mother o f thoughts and may be regarded as a picture of the Christ-child. The world cannot know itself unless it recognizes this kinship, according to Grundtvig.The most important task o f the Word is to bring life from God to man, not merely the Christian life, but the word for all things spiritual which are hidden from the eyes o f the world. When Grundtvig says it is only at baptism and the Eucharist that we hear the Word of God speaking to us, it must not be understood to mean a limitation on the scope of the Word of'God, but that in other places it is brought together with the human Word and its participation. In all discussion about God a conversation takes place between people about something that only God knows, but which a person can believe when he meets it and answers yes to His word - as at baptism and the Eucharist. In the poem Livets Ord (The Word o f Life) Sang-Værk 5-229, the Bible is called a letter from heaven, but not the book o f life. All human life is only a loan from the Creator’s breath; but this will first be revealed in eternity.The hymn Op til Guds Huus vi gaae (We are Going up to God’s House) is about the Word o f the Church. Originally this hymn described not only the Word o f God to man at baptism, but also (in a verse omitted in the Danish Hymn Book) the Word o f G od at the Eucharist. The verse in question says that at the Eucharist God kisses man in such a way as to give him a heavenly child mind. In Grundtvig’s hymns the kiss is not the lover’s kiss to his bride, but the Father’s kiss to His child. Grundtvig finds the same paternal love expressed in the Lord’s Prayer: only sons and daughters o f God can say this prayer, in a child-father relationship with God. The Word o f God in church is also the blessing. All speech in church must rest on the Church’s ancient words, which are few, as Jesus wished them to be. And whoever presents them cannot rule over them, but has them only, as it were, on loan; whereas whoever hears them receives them as a gift to be converted into deeds.In 1856 Grundtvig wrote a poem about the Bible and Christianity which expresses what was for him the curious thought that the Spirit o f God is sovereign in the orally transmitted word, because it is not »stolen« from the written word. The Bible is like a tree with many mysterious leaves that can inspire the poet - like birds who build their nests in the tree. It is not from the tree that they receive the very spirit they are singing from.When Grundtvig makes the spoken word sovereign over the written, it is because it was with the spoken word that God created Time - as the poem Havamal puts it - Poetical Works IX - 293. In 1863 Grundtvig wrote the poem Røsten (The Voice) on the same subject; an interpretation by Uffe Hansen is to be found in Grundtvig Studies 1958, pp36-46. In this poem man’s hymn o f thanksgiving is the » Heart’s Echo« o f God’s living voice which created the world.